Кваліфіковане мовчання законодавця: проблема розпізнання - Чалий, Ю. І.; Chaliy, Y. I.; ORCID: http://orcid.org/0000-0002-3641-0760 (Вісник Харківського національного університету внутрішніх справ. – 2019. – № 3 (86). – С. 22-31, 2019)
Критично оцінено спроможність системного тлумачення норм права як самодостатнього методу виявлення кваліфікованого мовчання законодавця. З метою розпізнання дійсного кваліфікованого мовчання законодавця запропоновано концентруватися на з’ясуванні правової політики, яка може виявлятися в тих чи інших випадках мовчазного виявлення волі законодавцем. При цьому відносно потреби з’ясування правової політики історичне чи доктринарне тлумачення законодавства мають похідне значення.

The problem of developing the ways of recognition of the qualified silence of the legislator has been studied. It has been stated that the “qualified silence of the legislator” is underdeveloped category of law, especially regarding the ways of recognizing such specific legislative silence within the norms of law. This problem has become more urgent due to the revival of case law in Ukraine on the application of the analogy of law and the analogy of legislation. While applying these techniques, overcoming the gaps of civil law, the courts often identify the relevant gaps of the legislation with the qualified silence of the legislator, which is a major shortcoming. Solution of this problem will allow the courts to better identify the qualified silence of the legislator in the law norms. One of the methodological approaches in solving the problem of recognition of the legislator’s qualified silence and the gaps of the legislation is the extension of the relevant research tools. In contrast to the legal position existing in the legal doctrine, the author of the article has critically assessed the ability of systematic interpretation of the law norms to be a selfsufficient method of revealing the legislator’s qualified silence. In order to recognize the true qualified silence of the legislator, the author has offered to concentrate on explaining the legal policy that may be manifested in one or other cases of the legislator’s silent expression of will. At the same time, systematic, historical or doctrinal interpretation of legislation is of relative importance to the need for clarifying legal policy. From the point of view of determining the degree of scientific novelty, the suggested approach has the nature of further development of doctrinal provisions. The author has noted on the necessity of further elaboration of the studied problems, in particular, in determining the location of each of the ways of recognizing the qualified silence of the legislator within the system of methods of interpretation of legal norms.

Критически оценена способность системного толкования норм права как самодостаточного метода выявления квалифицированного молчания законодателя. С целью распознания настоящего квалифицированного молчания законодателя предложено сконцентрироваться на выяснении правовой политики, которая может проявляться в тех или иных случаях молчаливого изъявление воли законодателем. При этом в отношении необходимости выяснения правовой политики исторического или доктринарного толкования законодательства имеет производное значение.
Qualified Legislator’s Silence: Problem of Recognition
Чалий, Ю. І. Кваліфіковане мовчання законодавця: проблема розпізнання / Юрій Іванович Чалий // Вісник Харківського національного університету внутрішніх справ. – 2019. – № 3 (86). – С. 22-31. – DOI: https://doi.org/10.32631/v.2019.3.02.
Чалий, Ю. І. (2019) «Кваліфіковане мовчання законодавця: проблема розпізнання», Вісник Харківського національного університету внутрішніх справ, 86(3), с. 22-31. doi: 10.32631/v.2019.3.02.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; кваліфіковане мовчання законодавця; тлумачення норм законодавства; квалифицированное молчание законодателя; толкования норм законодательства; qualified silence of the legislator; interpretation of the norms of legislation